2017
DOI: 10.1136/bmjopen-2016-013868
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with participation in cervical cancer screening among young Koreans: a nationwide cross-sectional study

Abstract: ObjectivesDespite the possibility of early detection of cervical cancer, participation in screening programmes among young Koreans is low. We sought to identify associations between risk factors and participation in screening for cervical cancer among young Koreans.DesignNationwide cross-sectional study.SettingRepublic of Korea.Participants3734.Main outcome measuresThe Korea National Health and Nutrition Examination Survey (KNHANES V: 2010–2012) was used to evaluate factors associated with attendance for cervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
21
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 27 publications
9
21
1
1
Order By: Relevance
“…High response rate was observed in under-screened and never screened populations, indicating that the acceptability and feasibility of HPV self-sampling as an alternative primary screening are promising in Hong Kong. Our findings align with other jurisdictions that focused on the feasibility and evaluation on HPV self-sampling in cervical cancer screening due to its high sensitivity, high acceptability, and cost-effectiveness in health settings [ 24 , 25 , 26 ]. In addition to the experiences of other jurisdictions, our study provided substantial information for decision-making in health policy, implementation, and evaluation of the national cervical cancer prevention programme in Hong Kong.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…High response rate was observed in under-screened and never screened populations, indicating that the acceptability and feasibility of HPV self-sampling as an alternative primary screening are promising in Hong Kong. Our findings align with other jurisdictions that focused on the feasibility and evaluation on HPV self-sampling in cervical cancer screening due to its high sensitivity, high acceptability, and cost-effectiveness in health settings [ 24 , 25 , 26 ]. In addition to the experiences of other jurisdictions, our study provided substantial information for decision-making in health policy, implementation, and evaluation of the national cervical cancer prevention programme in Hong Kong.…”
Section: Discussionsupporting
confidence: 89%
“…As not many studies have explored factors associated with the uptake of HPV self-sampling but Pap smear testing (e.g., [ 27 ]), it was difficult to make a direct comparison with these studies. Nevertheless, it is worth noting that age, education level, household income, smoking and drinking frequency, and job status were associated with the uptake of cervical cancer screening [ 26 ]. Hence, more research on the uptake of HPV self-sampling and its associated factors is needed.…”
Section: Discussionmentioning
confidence: 99%
“…The results from this study revealed that the majority of the women in both groups married when they were young adults (20-24 years); however, this did not make them eager to come and get a CCS until they reached a certain age or symptoms presented themselves Income per month was found to be significantly correlated with CCS history (p=0.038). This finding supported other study by Chang, et al, (2017) who found that total income per month was significantly associated with women's participation to get a CCS in Korea. This could be due to the expensive cost of CCS in Indonesia.…”
Section: Resultssupporting
confidence: 83%
“…16,17 Selain itu, rendahnya penyampaian informasi kesehatan serta lingkungan pekerjaan tidak memberi izin dan tidak memfasilitasi pemeriksaan IVA juga menjadi latar belakang rendahnya partisipasi wanita bekerja dalam skrining kanker. 18 Tingkat pengetahuan memiliki hubungan yang bermakna secara statistik dengan pemanfaatan pemeriksaan IVA oleh peserta JKN-KIS. Hasil penelitian ini sejalan dengan Mirayashi, sedangkan penelitian Parapat menyatakan bahwa meskipun memiliki pengetahuan yang baik, tetapi rasa takut dan persepsi ibu mengenai penyakit yang ditemukan dini dapat membebani pikiran dapat menyebabkan rendahnya perilaku periksa IVA.…”
Section: Pembahasanunclassified